ANTAGONISTIC ACTIVITY OF SOIL ACTINOMYCETES AGAINST COMMON HUMAN PATHOGENS - DINESH PANWAR,; VIPIN K. SAINI, (International Journal of Pharma and Bio Sciences, 2012)
Antimicrobial activity of actinomycetes isolated from the soil was studied for the production of novel secondary metabolites. A total of 93 isolated actinomycetes were subjected to primary screening against human pathogenic Escherichia coli, Bacillus subtilis, Candida albicans and Aspergillus niger. Out of 93 actinomycetes, only 25 isolates showed the antagonistic activity against the test pathogens. Six isolates were effective against Escherichia coli, 10 were effective against Bacillus subtilis, 6 were effective against Candida albicans and 19 were effective against Aspergillus niger. Among them four isolates were effective against all the test pathogens. These four isolates were subjected to the secondary screening to test the broader spectrum activity. These isolates were identified by morphological and biochemical methods, 3 isolates were identified as Streptomyces spp. and one isolate as Micromonospora sp.